2015
DOI: 10.3177/jnsv.61.188
|View full text |Cite
|
Sign up to set email alerts
|

Flavones Inhibit LPS-Induced Atrogin-1/MAFbx Expression in Mouse C2C12 Skeletal Myotubes

Abstract: Summary Muscle atrophy is a complex process that occurs as a consequence of various stress events. Muscle atrophy-associated genes (atrogenes) such as atrogin-1/MAFbx and MuRF-1 are induced early in the atrophy process, and the increase in their expression precedes the loss of muscle weight. Although antioxidative nutrients suppress atrogene expression in skeletal muscle cells, the inhibitory effects of flavonoids on inflammation-induced atrogin-1/MAFbx expression have not been clarified. Here, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 37 publications
(29 reference statements)
4
37
0
Order By: Relevance
“…Analyses of the protective effects of various flavonoids against lipopolysaccharide-induced MAFbx expression in skeletal myotubes revealed that two major flavones, apigenin and luteolin, prevented the decrease in myotube diameter and suppressed MAFbx promoter activity [143]. Similarly, the phyto-polyphenols epicatechin, epicatechin gallate, epigallocatechin gallate, and quercetin, were found to attenuate the increase in MuRF-1 and MAFbx induced in skeletal myotubes by three dimensional clinorotation [144].…”
Section: Plant Extracts and Antioxidant Phytochemicalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Analyses of the protective effects of various flavonoids against lipopolysaccharide-induced MAFbx expression in skeletal myotubes revealed that two major flavones, apigenin and luteolin, prevented the decrease in myotube diameter and suppressed MAFbx promoter activity [143]. Similarly, the phyto-polyphenols epicatechin, epicatechin gallate, epigallocatechin gallate, and quercetin, were found to attenuate the increase in MuRF-1 and MAFbx induced in skeletal myotubes by three dimensional clinorotation [144].…”
Section: Plant Extracts and Antioxidant Phytochemicalsmentioning
confidence: 98%
“…Again, most of the evidence for these lifestyle effects on PS-341 [130] Dietary amino acids Leucine [129,[132][133] BCAA [136][137] Arginine [137] Glutamine [138] Taurine [139] Redox-related inhibitors N-acetylcysteine [39] Procysteine [120] Allopurinol [140] Phytochemicals Curcumin [141][142] Flavonoids [143] Polyphenols [144][145] PMI5011 [146] Ursolic acid [147] …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…reported that AP administration to obese mice ameliorated metabolic disease; decreases in protein acetylation and modulation of glucose and lipid homeostasis by increases in cellular NAD+ levels acted as inhibitors of the NAD + ase CD38. Although AP was suggested to have inhibitory effects on atrogin‐1/MAFbx expression and prevented the decrease in myotube diameter in C2C12 cells caused by lipopolysaccharide stimulation, the mechanisms of action of AP remain largely unknown and the biological effects of AP on obesity‐induced muscle atrophy have not yet been demonstrated in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Apigenin [5,7-dihydroxy-2-(4-hydroxyphenyl)-4H-1-benzopyran-4-one] is a naturally occurring plant flavone with anti-obesity, anti-inflammatory, antioxidant, and anti-cancer properties. [9][10][11] Moreover, Shiota et al 12 reported that apigenin (AP) has inhibitory effects on atrogin-1/MAFbx expression and prevents reductions in myotube diameter induced by lipopolysaccharide stimulation in the C2C12 murine cell line. However, the biological effect of AP in denervationinduced muscle atrophy has not yet been demonstrated.…”
mentioning
confidence: 99%